Corporate governance in Islamic Banks from an Islamic perspective / Irum Saba and Ahcene Lahsasna - Saba, Irum; Lahsasna, Ahcene (2013)
Purpose - Corporate governance is crucial for the sustainable development of any corporate entity including Islamic banks. Islamic ethics, values and governance should be inbuilt in Islamic banking operations. The purpose of this paper is to discuss corporate governance from the Islamic perspective in relations to Islamic banking with special focus on Malaysia. This paper focuses on the structure of corporate governance, its implementation and relationship with Shariah governance and related parties in Islamic banking by addressing relevant issues and challenges.